A prospective longitudinal relation between elevated use of electronic devices and use of electronic nicotine delivery systems. (November 2019) - Lee, Shieun; Han, Dae-Hee; Chow, Angela; Seo, Dong-Chul
Abstract: Background: In recent years, there has been a rapid increase in the use of both electronic nicotine delivery systems (ENDS) and electronic devices among U.S. youth. Informed by the Diffusion of Innovations Theory (DIT), it was hypothesized that elevated use of electronic devices (EUED) prospectively would predict ENDS use among youth. Methods: Data were drawn from the Population Assessment of Tobacco and Health (PATH) Study, a longitudinal cohort study in a nationally representative sample. Participants who were 12–17 years old, and naïve to both conventional cigarettes and ENDS at baseline ( N  = 11, 325) were sampled. A total of 8723 respondents had matched data from Wave 1 to Wave 2 and 6051 respondents had matched data for all the three waves. Multivariable sequential logistic regressions were conducted to examine determinants of ENDS use in later waves using R version 3.5.2. Results: Among youth who were naïve to both ENDS and conventional cigarettes at baseline, those with EUED were more likely to initiate ENDS use in later years than those without EUED even after controlling for exposure to ENDS advertisements and other well-established covariates of ENDS use. Daily (adjusted odds ratio [AOR] ranges from 2.76 to 3.56) and weekly (AOR ranges from 2.16 to 2.65) social networking service (SNS) users were more likely to initiate ENDS use than non-users of SNS in the adjusted models. Conclusions: The findings support the hypothesis that EUED prospectively predicts ENDS use among youth. The use of DIT framework helps understand the link between EUED and ENDS use. Highlights: Elevated use of electronic devices (EUED) prospectively predicts ENDS use in youth. Diffusion of Innovations Theory helps understand the link between EUED and ENDS. Daily and weekly SNS users are more likely to initiate ENDS use than non-users of SNS.